(untitled) (Journal of Informatics and Mathematical Sciences, 2018)
The object of the present paper is to study anti-invariant submanifolds \(M\) of \((LCS)_n\)-manifold \(M\). The basic equations are decomposed into horizontal and vertical homomorphisms and geometric properties of anti-invariant submanifolds are studied.